Studi Kualitatif tentang Kebutuhan Implementasi Coaching dalam Supervisi Akademik untuk Meningkatkan Kualitas Pembelajaran Guru - Jatmiko, Heri; Hartinah, Sitti; Apriani, Dewi (Jurnal Simki Pedagogia, 2025)
This research aims to explore the factors that influence the implementation of Coaching in academic supervision to enhance the quality of teaching at SMP Negeri 2 Balapulang. A qualitative case study method was used, with data gathered through in-depth interviews, observations, and document analysis. The findings indicate that school principals recognize the significance of Coaching to support their roles as facilitators of learning. Teachers expressed a desire for more reflective supervision that facilitates their professional growth. Key factors contributing to the successful implementation of Coaching include teachers' willingness to embrace change and a well-organized supervision schedule. However, challenges such as the lack of formal Coaching training, authoritarian leadership styles, and the principals' heavy administrative duties were identified. The study suggests the development of Coaching programs that are tailored to meet the specific needs of schools and the adoption of more humanistic and collaborative supervision policies. It is anticipated that these changes will lead to improved teaching quality and promote continuous professional development for teachers.